Profile of leprosy in children under 15 years of age monitored in a Brazilian referral center (2004-2012) - Ana Cecília Versiani Duarte Pinto; Patrick Alexander Wachholz; Gardenia Viana da Silva; Paula Yoshiko Masuda (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Leprosy in children under 15 years of age is a serious public health problem. In this retrospective case series conducted in a Brazilian reference center (2004-2012), we found 18 cases with a mean age of 10.0±3.6 years of age and 16.6% between 0-5 years of age. Almost 56% of the cases were female, with a median time between the first symptoms and diagnosis of 11 months (4-24); 77.8% reported household contact with leprosy patients. Upon hospital admission, 66.7% presented mostly skin symptoms, while 27.8% presented a degree 2 disability. Most were classified as multibacillary (66.7%). Half of the sample developed a reaction (predominantly type 1) during the follow-up period, while 22.2% developed a late disability.